Vitamin D Status among Patients Visiting an Urban Tertiary Care Hospital, Dhaka - Raihan, Kazi Fahmita; Anwar, Taznuva; Khatun, Shahana (IAHS Medical Journal, 2024)
Background: Majority of the Bangladeshi population lives in an areas receiving ample sunshine throughout the year. Despite this fact multiple studies have shown wide prevalence of vitamin D deficiency in our country in all ages and both sexes. Adequate vitamin D status has an important clinical advantage for maintaining various activities as well as preventing diseases. In this lab based retrospective study, it was determined the prevailing condition of vitamin D deficiency among adult patients visiting MH Samorita Hospital and Medical College outdoor. The present study aimed to focus on assessing Vitamin D status of adult patients visited a tertiary care hospital of Dhaka city. Materials and methods: This was a retrospective study. A total of 72 cases were chosen by random sampling with records of vitamin D status, age and sex from July to December, 2022.The results were statistically analyzed with Statistical Packages for Social Science (SPSS-24). Results: Out of total subject (n=72) none of them showed toxic serum concentration of vitamin, 12.5 % had sufficient, 23.6% had insufficient and 63.9% had deficient levels of vitamin D. Gender wise comparison of vitamin D status showed male patients, 28.3% were deficient in vitamin D, 47.1% were insufficient, and a substantial 77.8% had sufficient levels. In contrast, a much higher proportion of female patients were deficient (71.7%) or insufficient (52.9%) in vitamin D, with only 22.2% having sufficient levels. According to age wise distribution, the highest percentage of vitamin D deficiency (58.7%) was observed in the youngest age group (18-30 years), while the proportion decreased in older age groups (30.4% for 31-50 years and 10.9% for 51-65 years). Conclusion: Vitamin D is an important vitamin which impacts many systems of the body .This study indicates that 63.9 % of subjects are vitamin D deficient which is very much alarming. So, it becomes paramount to further scrutinize the associated factors apart from age and gender. To this end, further studies are needed. IAHS Medical Journal Volume 6(2) December 2023; 68-72